IMPLEMENTASI TEAMS GAMES TOURNAMENTS (TGT) BERBANTUAN MEDIA KARTU 4-1 UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR IPS PESERTA DIDIK KELAS IX F DI SMPN 1 KANDEMAN BATANG 2014/2015 - Aryani, Wulan Dwi (Faculty of Social Science, Universitas Negeri Semarang, 2015)
This research aims to: (1) know the implementation of Teams Games Tournaments (TGT) Assisted by Card 4-1, (2) improve student social skills (3) increase social sciences learning outcome of IX F graders at SMPN 1 Kandeman Batang with the implementation of TGT Assisted by Card 4-1.This is a class action research using the spiral design of Kemmis & Taggart. Research subject is 37 students of IX F graders of SMP Negeri 1 Kandeman Batang in genap semester academic year of 2014/2015. There are 2 cycles in this research, each of which consists of two meetings. Each cycle uses 4 stages, they are: planning, implementation, observation and reflection. The action in cycle 1 uses card 4-1 with the materials of geographical elements and population in South East Asia. Cycle 2 uses card 4-1 with the material of earth surface division as continent and ocean. The research is conducted from January to March 2015. Data collecting technique used in this research is: (1) observation, (2) interview, (3) learning outcome test, (4) documentation, and (5)field note. The instrument used is (1) observation guidance for teacher and students, (2) interview guidance for students, (3) exercise sheet for learning outcome test, and (4) daily journal. Data analysiss uses qualitative analysis. The results of the research are: (1) The cooperative TGT Assisted by Card 4-1 learning model can be implemented in social sciences learning of IX F graders at SMP N 1 Kandeman Batang, there is average increase from 6 cycles of TGT, the average score of cycle I is 68,75 (good) and cycle II is 85 (very good) (2) there is average increase of 10 indicators of student social skills, the average score of cycle I is 51,30 (skilled), cycle II is 76,80 (hihgly skilled). (3) there is an increase in the result of students' social sciences learning, learning mastery at cycle I is 72,97% with the average score of 74,86, cycle II is 86,49% with the average value of 85. With the implementation of Teams Games Tournament Assisted by Card 4-1 in each cycle, there is a significant increase in social skills, that is, giving opinion on some topic being discussed, giving opinion with the language that can be understood by other students, giving opinion well and politely, giving opinion in solving group problems, accepting other member's opinion as long as relevant with the topic being discussed, keep the peace of group forming. Thus, the implementation of Teams Games Tournament Assisted by Card 4-1 in social sciences learning can comprehensively increase student learning outcome.